INTEGRATING ENGLISH LITERATURE INTO LANGUAGE TEACHING: A COMPREHENSIVE ANALYSIS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This report examines the integration of English literature into language teaching, analyzing its pedagogical benefits, theoretical underpinnings, practical methodologies, and associated challenges. It highlights literature's capacity to significantly enhance linguistic competence, foster profound cultural awareness, cultivate critical thinking, and boost learner motivation. The discussion traces the evolution of literature's role in English Language Teaching (ELT) from historical translation tools to dynamic vehicles for communicative and holistic development.